The Students’ Perception On Writing Tools Application For Essay Writing Class - Lestari Setyowati; Fahmi Rizky Abiyasa; Ana Ahsana El-Sulukiyyah; Nova - Ariani (Jurnal Dimensi Pendidikan dan Pembelajaran, 2022)
The purpose of this study is to describe the students’ opinion 1) about writing in general, 2) the type of writing tools application used by the students in writing, 3) the most preferable writing tools application. The research uses a cross-section design. In this design, quantitative data collection and analysis are followed by qualitative data collection and analysis before the results are interpreted. The subject of this research was 32 fourth-semester students in English Education Study Program, Faculty of Pedagogy and Psychology of the University of PGRI Wiranegara, Pasuruan. The instruments used in this study were a questionnaire, interview, and documentation. The result reveals that half of the participants feel writing is difficult, while the other half feel writing is easy. Almost half of the students (47%) state that language/grammar is the most difficult element in writing. The types of writing tool applications used by the students are Grammarly (55%), U_Dictionary (24%), and Goggle Translate (21%). These writing tools help the students to solve the writing problems, such as in language, vocabulary, idea development, and drafting. The students think that writing tools application is practical and timesaving (74%). The students also believe that the writing tools application is beneficial and helpful to improve the quality of their essay. Interestingly, the students confess that they are uncertain if they can write well without writing tools application. Some of them feel that they cannot write well without the help of the application. The implication of the finding is discussed.